The Role of TNCs in the Extractive Industry of the United Republic of Tanzania - Kweka, Josaphat (2012)
Tanzania is richly endowed with mineral resources. Since the mid-1990s, the mining sector has been the fastest-growing sector in the economy, following adoption of favourable investment policies with specific measures for the mineral sector. The influx of FDI is having a net positive development impact, but which needs to be nuanced. First, the impact on the industry in terms of export revenue, employment, technology, skills and knowledge, and Government revenue is significant in absolute and relative terms, given the low base from which the industry grew. Secondly, the impact on local communities is also notable, however, the size of such contributions is largely disproportionate to the revenues accruing to the TNCs and the social cost of the environmental degradation associated with the mining operations. Finally, There is a lack of substantial economy-wide multiplier effects, as would be suggested by the "trickle-down" theorem; but this is purely a policy failure argument in that the lack of significant linkages to the rest of the economy arises from weak supply capacity and an incomplete supply chain. Policy recommendations are made based on a careful assessment of the wider social, political and economic dimensions.